2015
DOI: 10.1016/j.carbpol.2015.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent systems with cyclodextrins and hydrophilic polymers for the delivery of Efavirenz

Abstract: Efavirenz (EFZ) is one of the most used drugs in the treatment of AIDS and is the first antiretroviral choice. However, since it has low solubility, it does not exhibit suitable bioavailability, which interferes with its therapeutic action and is classified as a class II drug according Biopharmaceutical Classification System (low solubility and high permeability). Among several drug delivery systems, the multicomponent systems with cyclodextrins and hydrophilic polymers are a promising alternative for increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Solubility of EFV with grafted copolymer having 1:4 ratio of CS and HPβCD was found to increase solubility of EFV 380 times than that of the free drug. This increase in solubility is higher than the techniques reported earlier such as nanosuspension, 20 solid ternary system containing EFV, MβCD and PVP K30, 21 dendrimerization, 22 composite hydrogel containing HEC-PAA 23 and nanocrystalization. 24 It was observed that with the increase in ratio of HPβCD in graft copolymer (1:1, 1:2, 1:3, 1:4) solubility of EFV was also increased.…”
Section: Solubility Determinationmentioning
confidence: 71%
“…Solubility of EFV with grafted copolymer having 1:4 ratio of CS and HPβCD was found to increase solubility of EFV 380 times than that of the free drug. This increase in solubility is higher than the techniques reported earlier such as nanosuspension, 20 solid ternary system containing EFV, MβCD and PVP K30, 21 dendrimerization, 22 composite hydrogel containing HEC-PAA 23 and nanocrystalization. 24 It was observed that with the increase in ratio of HPβCD in graft copolymer (1:1, 1:2, 1:3, 1:4) solubility of EFV was also increased.…”
Section: Solubility Determinationmentioning
confidence: 71%
“…Similar approaches have already been reported for different ternary systems, where solubility, stability and potency were modified. For example Vieira, A. C. et al 33 described an increase of solubility and stability for efavirenz according to ternary system formation containing methyl-b-cyclodextrin and polyvinylpyrrolidone K-30. Wang, D. et al 34 noted the enlargement of the solubility and stability of dihydroartemisinin after preparing the ternary system with hydroxypropyl-b-cyclodextrin and lecithin.…”
Section: Resultsmentioning
confidence: 99%
“…This increase was mainly related to spherical shape of SCAs and by increasing in wettability due to the presence of different polymers. PEG 4000 show highest increase in rate of dissolution (f2=20.014) in comparison with pure drug dissolution rate that's because PEG 4000 have important effect on maintaining the spherical shape of agglomerated crystal (36) and also it enhances the physical and chemical stability of drugs and prevents aggregation of the drug particles as a result of the steric hindrance and/or masking of charges provided through formation of a conformational cloud (37) so, higher surface area will be available for dissolution. β.cyclodextrin and TPGS increase in dissolution of EBS (f2= 24.07294) and (f2= 39.46175) respectively due to improvement in solubility.…”
Section: In-vitro Dissolution Studymentioning
confidence: 99%
“…On other hand, FTIR spectrum of PEG 4000 show broad band at 3450.99 cm -1 due to O-H group stretching, intense peak at 2885.95 cm -1 due to C-H stretching in addition to an intense band at 1105.98 cm -1 of C-O group (43,44) . FTIR spectrum of the physical mixture of drug and polymers, spherical agglomerated SCAs (EBS1, EBS 6) show no significant shift or reduction in intensity of peaks of EBS, and of β. cyclodextrin, which indicate there was no interaction between drug and polymer.…”
Section: Ftir Studymentioning
confidence: 99%